Phylogeny of Aspergillus section Circumdati and inhibition of ochratoxins potential by green synthesised ZnO nanoparticles - Mohamed A. Hussein; Youssuf A. Gherbawy; Mahmoud S. Abd El-sadek; Helal F. Al-Harthi; Eman GAM El-Dawy (Mycology)
Contamination of agricultural and industrial products by Aspergillus section Circumdati becomes a true problem, especially, because a lot of species in this section can yield ochratoxins and other toxins. In this study, morphological criteria and partial calmodulin gene were used to identify 34 strains belonging to Aspergillus section Circumdati isolated from Vitis vinifera and Calotropis procera plants. The population is characterised by A. insulicola, A. ochraceopetaliformis, A. ochraceus, and A. pseudoelegans. The polyketide synthase (pks) gene involved in ochratoxins (OTA) production was investigated by Aopks1, 2 and AoLc35-12L, R primers. Fifteen strains belonging to A. ochraceus were positive for pks gene, whilst A. insulicola, A. ochraceopetaliformis, and A. pseudoelegans were negative. All tested strains were able to produce ochratoxin A with different levels of 0.020–53 ppm except one isolate of A. ochraceus (IAEMAo6). The green synthesised ZnO-NPs have a significant inhibitory effect on OTA production by A. insulicola and A. pseudoelegans.